Design, Implementation and Evaluation of a Student Mentoring Program for Pharmacy Students Based on Facilitation by the Pharmacist Assistant Website at the School of Pharmacy of Ahvaz Jundishapur University of Medical Sciences - Maryam Khajavi; Mandana Izadpanah; Kaveh Eslami; Leila Kouti (Research Center for Rational Use of Drugs (RCRUD), 2021)
Background: Mentoring is a learning and training process in which a qualified person with more experience (mentor) consults a person with fewer skills or less experience (mentee). The purpose of this study was to design, implement and evaluate the student mentoring program for entry Pharmacy students of academic year 2019-2020 (as mentees) and to use a website to communicate with students in order to use new methods of communication.Methods: In this project, 2015, 2016 and 2017 entry students were used as mentors. After assessing the needs of senior students, the mentoring program was designed and after revision, mentors and mentees were introduced to each other. Considering the outbreak of Corona virus in the middle of the project, the Pharmacist Assistant website was designed as a virtual learning platform and made accessible to students for keeping the mentoring members in touch with each other.Results: Preliminary results of a needs assessment showed that students prefer being consulted by senior students in the times of challenge. A survey of mentees showed that all mentees were satisfied with participating in the program and recommended its implementation, and almost half of them believed that the web design was successful in educating students during the pandemic.Conclusion: Due to the high satisfaction of the mentees with the mentoring program and their familiarity with the academic challenges before facing them, running mentoring programs can be very functional and helpful in Schools of Pharmacy. In the case of coronavirus pandemic, one way to prevent damage to the mentoring program and to keep the mentor and mentees in touch is to design a virtual platform such as the Pharmacist Assistant website.